Regulation resources in high-tech innovation development of economy of Ukraine - Захарченко, Наталія Вячеславівна (Technology audit and production reserves, 2015)
The role of h-tech recourse in modern economy is analyzed in the article. Model of innovation growth is considered as the more efficacious form of the state-business-science cooperation during creation and introduction of innovations. This model is a reflection of the new economic realities, including the knowledge economy, globalization, the integration of states and corporations, the new means of communication and technologies, network forms of organization. All these processes have led to an unprecedented acceleration of innovation development of the country. Special attention is devoted to the principles of innovation resource state regulation in modern economy. The article highlights the features of the application of foreign experience in the practice of Ukraine, which makes it possible to identify those components of the system of state support that have shown positive results in a number of countries. The study highlighted the types of organizations that would contribute to the strengthening of ties between the economy and science, as well as effectively at the level of the national innovation system, namely: 1) industrial parks, techno, incubators, research consortia, joint company, which can be created by the state, and private business. They are designed for the transfer and dissemination of new technologies; 2) innovation intermediaries government organizations: agency for the transfer of technology, various coordinating committees whose task is to develop interaction between corporations and agencies funded by the state in which conditions are created for the technological know-how; 3) hybrid coordinators, which are defined by various organizations such as agencies, technology transfer and the various coordinating committees. The author noted that the policy aimed at creating high tech resources, economic development, includes two areas: 1) create conditions for the development of education, public sector research and development in order to ensure a sufficient supply level of intellectual work; 2) the establishment of rules for organizing a network of scientific contacts.